The effects of supplemental dietary carnitine, betaine, and chromium nicotinate on growth and carcass characteristics in growing-finishing swine - J W Smith II; K Q Owen; K G Friesen; T T Lohrmann; S A Blum; Jim L Nelssen; Robert D Goodband; Michael D Tokach (Kansas Agricultural Experiment Station Research Reports, 1994)
Sixty-four pigs (initially 75 lb) were used to determine the effects of dietary betaine, carnitine, and chromium nicotinate on growth performance and carcass composition. Pigs were blocked by sex, ancestry, and weight and allotted in a randomized complete block design to each of four dietary treatments. These treatments were a corn-soybean meal-based control diet and control diet plus 50 ppm carnitine, 1,000 ppm betaine, or 200 ppb chromium from chromium nicotinate. Grower diets (75 to 125 lb) were formulated to contain 1.0% lysine and finisher diets (125 to 225 lb) were formulated to contain .8% lysine. All diets were com-soybean meal-based, were fed in meal form, and contained .15% L-Iysine HCl and 2.5% soy oil. When mean weight of pigs in a pen reached 225 lb, one pig per pen was selected at random and slaughtered to obtain carcass measurements. During the grower phase, pigs fed carnitine had greater ADG and feed efficiency (F/G) than pigs fed the control diet. However, during the finishing phase and overall, no differences were observed for ADG, F/G, or ADFI. Pigs fed carnitine had larger longissimus muscle area and greater percentage muscle than pigs fed the control or betaine diets. Also, pigs fed carnitine had lower tenth rib backfat thickness compared to those fed the control diet. Average backfat thickness was lower in the pigs fed camitine or chromium nicotinate than in pigs fed the control diet. These results indicate that additions of dietary carnitine and chromium nicotinate are viable means of increasing carcass leanness in growing-finishing pigs. Further study of the metabolism of carnitine, chromium nicotinate, and betaine is needed to examine possible modes of action in the growing-finishing pig.; Swine Day, Manhattan, KS, November 17, 1994
Keywords: Swine day; 1994; Kansas Agricultural Experiment Station contribution; no. 95-175-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 717; Swine; Betaine; Carnitine; Chromium nicotinate; Pigs; G/F